Beyond change management : advanced strategies for today's transformational leaders - Anderson, Dean, 1953- (Practicing organization development series., 2001)
Transform your organization! To truly transform your organization, you must learn to transform your own mindset. Beyond Change Management - the only book specifically about the interaction of leadership style, mindset, and the change process - revolutionizes leaders' approach to transformational change.